Pengembangan Media Pembelajaran Power Point Macro Berbasis Problem Based Learning Materi Besaran dan Pengukuran Sebagai Sumber Belajar Siswa Kelas X - Miswati Miswati; Ahmad Amin; Endang Lovisia (SILAMPARI JURNAL PENDIDIKAN ILMU FISIKA, 2020)
This study aims to "Develop Macro Power Point Learning Media Based on Problem Based Laerning on Quantity and Measurement Materials as Learning Resources for Class X Students". Problems in this study 1) How to develop problem-based learning media for power point learning on quantity and measurement material as a learning resource for class X students ?, 2) What are the characteristics of the learning media for power point macro based on problem based learning that has been developed to meet validity and practicality?, 3) How do students respond during learning using power point macro learning media based on problem based laerning ?. The development model used is Borg and Gall. There are 10 stages, namely: potential and problem stages, data collection, product design, design validation, design revision, product testing, product revision, usage testing, product revision and mass production. The research subjects of class X MIPA SMA AL-IKHLAS Lubuklinggau used purposive sampling technique. Data collection was carried out by means of observation, interview and questionnaire techniques. The validation was carried out to get results in a very good category with a score of 128. The instrumentation used to measure student responses was using a questionnaire. The student response was a limited group and the teacher got a score of 146 in the strongly agree category. The response of the main field testing group was by completing the 6 students' quiz questions based on KKM. For the student response questionnaire the main field testing group got a score of 312 in the strongly agree category. So it can be said that the learning media for power point macro based on problem based learning that has been developed are valid and practical.